The Suitability of Students in Bachelor of Science in Statistics (BSS) Program - Casinillo, Leomarich F.; MiÃ±oza, Susana B (LPPM Undiksha, 2020)
This study aims to assess the suitability of students in Bachelor of Science in Statistics program. Seemingly, several students who enrolled in the said program does not possess the qualities of being mathematically inclined. Hence, this study was conducted.Â By complete enumeration, the study employed all BSS students from different year level. Secondary data were used such as two psychological tests from the University Student Services Office which measures the intelligence and numerical aptitude.Â A primary data was also employed through an instrument called Brainard Occupational Preference Inventory which measures the interest of students in the field of statistics. The gathered data were then analyzed with the aid of some descriptive measures and correlational methods. Results revealed that there are only a few (11.9%) who have high levels of intelligence and numerical aptitude but they happen to have low level of interest in statistics. Of those students highly interested (47.6%) in the field of statistics one-fourth (11.9%) of them have low levels of intelligence and numerical aptitude. It is found out that there is a significant linear relationship between intelligence and numerical aptitude among BSS students. Moreover, intelligence and interest in statistics is inversely and significantly correlated among BSS junior students. Furthermore, results showed that there is no significant linear relationship between numerical aptitude and interest in statistics across year level. Hence, the interest of the BSS students must be cultivated in order to increase their level of achievement.